2004
DOI: 10.1002/smi.998
|View full text |Cite
|
Sign up to set email alerts
|

Stress, symptoms of depression and anxiety, and cortisol patterns in working parents

Abstract: Whether stress or psychological distress is associated with alterations in diurnal cortisol secretion patterns in healthy adults is still uncertain. In this study, the authors tested for associations between stress or symptoms of depression or anxiety and changes in diurnal cortisol patterns in 91 working parents (57 women and 34 men) across the United States. Saliva samples were collected for cortisol analysis at six timepoints over 2 days. The diurnal cortisol slope and time‐weighted average cortisol levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 52 publications
1
21
0
3
Order By: Relevance
“…As the IES scores change, so too does the cortisol response when comparing categories of IES scores. The co-morbidity of PTS and depression has been noted by others (Conner & Butterfield, 2003;Franklin & Zimmerman, 2001;Kurina, Schneider, & Waite, 2004). This finding was also noted in the BCOPS Study, with the mean score of the depression index (CES-D) also increasing significantly across PTS categories.…”
Section: Discussionsupporting
confidence: 54%
“…As the IES scores change, so too does the cortisol response when comparing categories of IES scores. The co-morbidity of PTS and depression has been noted by others (Conner & Butterfield, 2003;Franklin & Zimmerman, 2001;Kurina, Schneider, & Waite, 2004). This finding was also noted in the BCOPS Study, with the mean score of the depression index (CES-D) also increasing significantly across PTS categories.…”
Section: Discussionsupporting
confidence: 54%
“…Researchers have found perceived stress associated with increased (Edwards et al , 2003), decreased (O’Connor et al , 2009), or no significant difference (Lovell et al , 2011) in the cortisol waking response. Some studies have shown perceived stress associated with a flattened diurnal slope (Lovell et al , 2011; Farag et al , 2008), but others have found no significant effect (Kurina et al , 2004; Abercrombie et al , 2004). Results are also conflicting for the effects on average diurnal output (O’Connor et al , 2009; Lovell et al , 2011; Kurina et al , 2004; Edwards et al , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that when the stress response is moderate and therefore concentrations remain below the CBG binding point, free cortisol appears to be representative of total cortisol (28)(29)(30) . However, previous studies which used different exercise intensities to assess the relationship between free and total cortisol have found differing results (9 10) .…”
Section: *--------------------------------------Figures 4 5 and 6 Nementioning
confidence: 99%